Immunogenicity and Safety of 13-valent Pneumococcal Conjugate Vaccine Compared With 7-valent Pneumococcal Conjugate Vaccine Among Healthy Infants in China. Issue 9 (September 2016) - Zhu, Fengcai; Hu, Yuemei; Li, Jingxin; Ye, Qiang; Young, Mariano M.; Zhou, Xin; Chen, Zhangjing; Yan, Bing; Liang, John Z.; Gruber, William C.; Giardina, Peter C.; Scott, Daniel A.
Abstract : Background: Immunogenicity and safety of 13-valent pneumococcal conjugate vaccine (PCV13) were compared with 7-valent pneumococcal conjugate vaccine (PCV7) in Chinese infants. Methods: Healthy infants aged 2 months were randomized to a double-blind 3-dose infant series plus 1 toddler dose of PCV7 or PCV13 at 3, 4, 5 and 12 months or open-label PCV13 at 2, 4, 6 and 12 months. Serotype-specific immunoglobulin G (IgG) binding and functionality were measured 1 month after the infant series and after the toddler dose. Local reactions, systemic events and adverse events were assessed postvaccination. Results: For the 7 common serotypes, serotype-specific binding IgGs elicited by PCV13 were noninferior to PCV7 after the 3-dose infant series; functional antibodies were comparable. For the 6 additional serotypes, PCV13 recipients had significantly higher serotype-specific IgGs and functional antibodies than PCV7 recipients after the infant series. The toddler dose boosted the immune response. Local reactions and systemic events were mild in severity and similar across groups. No new safety signals were identified. Conclusions: For the 7 common serotypes, serotype-specific binding IgG after 2 different 3-dose regimens of PCV13 were noninferior to PCV7 responses. PCV13 recipients had significantly higher immune responses to the 6 additional serotypes. PCV13 is expected to provide pneumococcal disease protection comparable to PCV7 for the common serotypes and further protection against disease caused by the 6 additional serotypes. Safety of PCV7 and PCV13 was comparable. Abstract : Supplemental Digital Content is available in the text.